PENGARUH BANTUAN SOSIAL PROGRAM KELUARGA HARAPAN (PKH), BANTUAN PANGAN NON TUNAI (BPNT) DAN BANTUAN SOSIAL TUNAI (BST) TERHADAP PENGURANGAN TINGKAT KEMISKINAN DI DESA DI WILAYAH KABUPATEN BARRU - SUARNI SUARNI; Sylvia Sjarlis; M Salim S (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
This study aims to determine the effect of social assistance program, the family program hope (PKH), for non-cash food assistance (BPNT) and cash social assistance (BST) to reduce poverty levels. The number of samples used is 40 villages with quantitative research methods. Data was collection through secondary data. Data analysis techniques used path multiple linears regression. The results show that (1) programs for families of hope (PKH) have a positive and significant effect on reducing poverty levels with a significance value of 1.858 (2) the non-cash food assistance program (BPNT) has no positive and significant effect on reducing poverty levels with a coeffient value of -0,244 (3) cash social assistance (BST) has no positive and significant effect on reducing poverty levels with a coefisient value of -0,139 (4). Program for family hope (PKH) for non-cash food assistance (BPNT) and cash social assistance (BST) have a fositive and sdignificant effect on 45,6 %.